Download presentation

Presentation is loading. Please wait.

Published byIrea Kerr Modified over 2 years ago

1
Algebra Expressions equations and solving equations

2
Energiser Which of these are true? = = = x 3 = 3 x 2 2 x 3 x 4 = 3 x 2 x 4 2 x x 3 = 5 x 3 2 x x 5 = 5 x 5 true false true

3
2 x 3 3 x 3 5 x = = 2 x 4 3 x 45 x 4+ = +=

4
2 x c 3 x c5 x c+ = + = Cost = c Check by substituting values.

5
Can you make 22 ? x x x Can you make 21?

6
a b cm n

7
a b cm n What is 2b + c ? 2b + c = 20 Can you make 20 another way ?

8
a What does a represent?

9
a The length of a fence

10
aaaaaaaaaa

11
ab

12
aab

13
aaabb

14
aaabb

15
ababa

16
ababaaaabb

17
ababa

18
ababa3 3a + 2b + 3

19
aaa3 If this was the fencing arrangement at the front of my garden and my garden is 9m long, how long is each fence? 9

20
aaa3 9 3a + 3 = 9

21
aaa 3a = 6 6

22
aaa a =

23
aaa 4 If this was the fencing arrangement at the front of my garden and my garden is 40m long, how long is each fence? 40 a

24
aaa 4 a 4a + 4 expression equation 4a + 4 = 40

25
aaa 36 a 4a = 36 aaa 4 40 a 4a + 4 = 40

26
aaa a = a 4a + 4 = 40 4a =

27
One person thinks of a length for a fence and gives it a letter. The person then draws some of the fences with a length added on. The rest of the group have to write an expression for the total length. The person then tells the group the total length and the group have to write an equation. The group then solve the equation and asks if the solution is right. Another person starts back at the beginning. Task 1

28
What about subtraction?

29
aaa 4a - 2 a 2

30
aaa a 2 10 = 10

31
aaa 4a = 12 a 12

32
aaa a = 3 a

33
One person thinks of a length for a fence and gives it a letter. The person then draws some of the fences with a length subtracted. The rest of the group have to write an expression for the length left. The person then tells the group the length left and the group have to write an equation. The group then solve the equation and asks if it is right. Another person starts back at the beginning. Task 2

34
b 3 bbbbb 7 bb 3b + 7 5b + 3 3b + 7 = 5b + 3

35
bbbbbb 7 bb 3b + 7 5b 3b + 7 = 5b + 3

36
bbbbbbbb 3b +4 5b 4 3b = 5b b + 7 = 5b + 3

37
bbbbbbbb 3b +4 5b 4 3b + 4 = 5b 3b = 5b b + 7 = 5b + 3

38
bb 4 2b 3b + 4 = 5b 3b = 5b b + 7 = 5b + 3

39
bb 4 2b 3b b = 5b - 3b 3b + 4 = 5b 3b = 5b b + 7 = 5b + 3

40
bb 4 = 2b 4 2b 3b b = 5b - 3b 3b + 4 = 5b 3b = 5b b + 7 = 5b = 2b 3b + 4 = 5b 3b = 5b b + 7 = 5b + 3

41
bb 4 = 2b 4 2b 3b + 7 = 5b + 3 3b + 4 = 5b 3b = 5b b + 7 = 5b = 2b 3b + 7 = 5b + 3 3b + 4 = 5b 3b = 5b b + 7 = 5b = b

Similar presentations

© 2016 SlidePlayer.com Inc.

All rights reserved.

Ads by Google